2015
DOI: 10.1016/j.virusres.2015.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Functions of the 5′ and 3′ ends of calicivirus genomes

Abstract: HighlightsNoroviruses are now recognized as the most common cause of viral gastroenteritis.The 5′ and 3′ ends of caliciviruses genome fold into characteristic structures conserved within the family.The tirmini of calicivirus genome is involved in recruiting host factors to the replication complex.The 5′ and 3′ ends of the MNV genome have been shown to interact with host proteins and further stabilize this interaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 62 publications
1
51
0
Order By: Relevance
“…For instance, during vRNA replication of RNA viruses, vRI-dsRNAs must be efficiently unwound, thereby releasing nascently synthesized progeny vRNAs from vRNA templates. Moreover, viral genomic and antigenomic RNAs contain multiple cis-acting elements, highly structured RNA regions that usually play pivotal roles in the replication, translation, and encapsidation of vRNAs (11,51). Sometimes, a specific RNA structure required for one vRNA function, like translation or encapsidation, may need disruption and refolding to facilitate another vRNA function, like vRNA replication, and vice versa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, during vRNA replication of RNA viruses, vRI-dsRNAs must be efficiently unwound, thereby releasing nascently synthesized progeny vRNAs from vRNA templates. Moreover, viral genomic and antigenomic RNAs contain multiple cis-acting elements, highly structured RNA regions that usually play pivotal roles in the replication, translation, and encapsidation of vRNAs (11,51). Sometimes, a specific RNA structure required for one vRNA function, like translation or encapsidation, may need disruption and refolding to facilitate another vRNA function, like vRNA replication, and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…For many RNA viruses, the viral RNA (vRNA) contains multiple cis-acting elements that play pivotal roles in vRNA replication, translation, and encapsidation during the viral life cycle (11)(12)(13). As with cellular RNA molecules, these elements are often highly structured in vRNAs and must be folded into the correct tertiary structures to be functional.…”
mentioning
confidence: 99%
“…The family Caliciviridae is currently divided into five genera: Vesivirus, Lagovirus, Norovirus, Sapovirus, and Nebovirus. [1][2][3][4] Infections with noroviruses (NoVs) and sapoviruses (SaVs) are a global public health concern because they cause acute gastroenteritis outbreaks in people of all ages, and infections are difficult to prevent and control. 5,6 Efficient cell culture systems for human NoVs and SaVs have not been established.…”
Section: Introductionmentioning
confidence: 99%
“…Discrete and conserved regions of the NoV genome contain the CRE at the 3¢ extremity of MNV and the sgRNA promoter, with a very high probability of conforming to a stem-loop structure [9,45]. Mutational analyses of MNV revealed that the stem-loop structures located at the 5¢ end of the genome are important for viral replication and that even synonymous mutations destabilize the stem-loop structures starting at the 5¢ end of the genomic and sgRNA [46]. Although the precise mechanism of internal ribosome entry site (IRES)mediated translation is unknown in picornaviruses, it has been suggested that they function as RNA chaperones to promote the correct folding of the RNA structure, facilitating the recruitment of translation initiation factors [47].…”
Section: Discussionmentioning
confidence: 99%